Visualization of accessible cholesterol using a GRAM domain-based biosensor - Koh, Dylan Hong Zheng (2024)
Cholesterol is important for membrane integrity and cell signaling, and dysregulation of the distribution of cellular cholesterol is associated with numerous diseases, including neurodegenerative disorders. While regulated transport of a specific pool of cholesterol, known as "accessible cholesterol", contributes to the maintenance of cellular cholesterol distribution and homeostasis, tools to monitor accessible cholesterol in live cells remain limited. Here, we engineer a highly sensitive accessible cholesterol biosensor by taking advantage of the cholesterol-sensing element (the GRAM domain) of an evolutionarily conserved lipid transfer protein, GRAMD1b. Using this cholesterol biosensor, which we call GRAM-W, we successfully visualize in real time the distribution of accessible cholesterol in many different cell types, including human keratinocytes and iPSC-derived neurons, and show differential dependencies on cholesterol biosynthesis and uptake for maintaining levels of accessible cholesterol. Furthermore, we combine GRAM-W with a dimerization-dependent fluorescent protein (ddFP) and establish a strategy for the ultrasensitive detection of accessible plasma membrane cholesterol. These tools will allow us to obtain important insights into the molecular mechanisms by which the distribution of cellular cholesterol is regulated.